Extension FAS Report of Accomplishments for 2003: A Guide to the Extension Portion of Your FAS ROA in 10 Pages or Less - Keith R. Schneider; Renee M. Goodrich; Howard W. Ladewig; Cheri A. Brodeur (EDIS)
The purpose of this fact sheet is to provide guidance in completing the FAS Extension Program Tab of the Report of Accomplishments for 2003. The Guidelines will emphasize being concise and the use of bullet statements. This document is RFSR025, one of a series of the Extension Administration Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2003.